2018
DOI: 10.1155/2018/3082560
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diabetic Macular Edema with Intravitreal Antivascular Endothelial Growth Factor and Prompt versus Deferred Focal Laser during Long-Term Follow-Up and Identification of Prognostic Retinal Markers

Abstract: Purpose Long-term follow-up of patients with diabetic macular edema (DME) treated with intravitreal antivascular endothelial growth factor (anti-VEGF) combined focal laser and identification of prognostic morphological characteristics. Methods Prospective clinical trial (50 treatment-naive eyes) with DME randomized 1 : 1 receiving intravitreal ranibizumab (0.5 mg/0.05 ml) and prompt grid laser compared with ranibizumab and deferred laser. Morphological characteristics potentially relevant for prognosis were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(34 reference statements)
1
4
0
2
Order By: Relevance
“…In our study, a signi cantly decreased HF could be found under adequate anti-VEGF treatment. This result is consistent with the results observed in previous studies that hyperre ective foci or spots decreased after anti-VEGF treatment [18,14,10]. The exact formation mechanism of HF remains still unclear despite several theories have attempt to explain the special marker.…”
Section: Discussion/conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, a signi cantly decreased HF could be found under adequate anti-VEGF treatment. This result is consistent with the results observed in previous studies that hyperre ective foci or spots decreased after anti-VEGF treatment [18,14,10]. The exact formation mechanism of HF remains still unclear despite several theories have attempt to explain the special marker.…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Similar progress has been made in patients with DME because OCT has been able to identify various pathologies in these patients, such as CMT, HF, SF, EZ/ELM irregularity and DRIL, and these ndings have begun to clarify the pathogenesis and prognosis of the disease. A large number of studies have been conducted on DME patients receiving anti-VEGF injections, and it has been con rmed that the microstructural changes seen at the baseline by OCT scans can predict the treatment response [14,10,15]. The TCED-HFV classi cation, as a non-invasive diagnostic method, had shown its potential for early diagnosis of DME and could quantitatively response the therapeutic effect to anti-VEGF treatment.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…DME with HRF has been associated with a poorer visual outcome following treatment with intravitreal steroid and anti-VEGF agents [14]. Clusters of HRF occupying the central macular area was associated with worse visual acuity than eyes without HRF clusters before any treatment, and the functional difference was maintained following intravitreal ranibizumab and focal laser therapy for up to 5 years [50].…”
Section: Clinical and Prognostic Implications Of Hyperreflective Foci In Diabetic Macular Edemamentioning
confidence: 99%
“…Wichtige Parameter sind der Visus, die Dicke der Netzhaut im Makulabereich, die Fläche des diabetischen Makulaödems und der klinische Verlauf. In der Regel besteht dann ein "klinisch relevantes diabetisches Makulaödem mit Notwendigkeit einer Therapie", wenn mit einer Fluoreszenzangiografie oder mittels SD-OCT (Spectral-Domain-OCT) ein diffuses Makulaödem mit zentraler Netzhautdicke (CRT) ≥ 300 μm im Zentrum der Makula nachgewiesen wurde und ein Visus schlechter 0,8 besteht [5]. In der VISTA-Studie war die Indikation für eine intravitreale Anti-VEGF-Injektion eine Verdickung der Netzhaut innerhalb des zentralen 1-mm-Teilfeldes und ein Visus schlechter 0,5.…”
Section: Diabetisches Makulaödem In Diabetologischen Schwerpunktpraxenunclassified